Silencing of TGF-β1 in tumor cells impacts MMP-9 in tumor microenvironment - Lakisha D. Moore-Smith (Nature Portfolio, 2017)
Abstract Transforming growth factor (TGF)-β1 contributes to autocrine and paracrine functions in the tumor microenvironment (TME). The present study examined the effects of TGF-β1 crosstalk in TME and its role in mediating tumor formation and progression by targeted abrogation of TGF-β1 expression in metastatic cells in situ. Using species-specific primers, we found a significant increase in MMP-9 gene expression in the tumor-reactive stroma during late-stage metastasis in the lung. This effect was also confirmed in cancer-associated fibroblasts (CAFs) when co-cultured with the tumor cells. Knockdown of TGF-β1 expression in the tumor cells negatively affected matrix metalloproteinase (MMP)-9 gene expression. Fibroblasts, cultured in the presence of tumor cells with intact TGF-β1, showed a significant increase in proliferation rate, as well as expression of VEGF, bFGF, and SDF-1, which was not seen when TGF-β1 expression was abrogated in tumor cells. Absence of TGF-β1 in tumor cells also failed to result in myofibroblast differentiation. Co-implantation of CAFs and tumor cells with either intact TGF-β1 expression or devoid of TGF-β1 in vivo showed a significant increase in tumor growth kinetics in both cell types, suggesting a possible activation TGF-β receptor signaling in tumor cells in response to TGF-β from the TME.